2015
DOI: 10.1007/s11434-014-0699-2
|View full text |Cite
|
Sign up to set email alerts
|

Why models run hot: results from an irreducibly simple climate model

Abstract: An irreducibly simple climate-sensitivity model is designed to empower even non-specialists to research the question how much global warming we may cause. In 1990, the First Assessment Report of the Intergovernmental Panel on Climate Change (IPCC) expressed ''substantial confidence'' that near-term global warming would occur twice as fast as subsequent observation. Given rising CO 2 concentration, few models predicted no warming since 2001. Between the pre-final and published drafts of the Fifth Assessment Rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(54 citation statements)
references
References 38 publications
2
51
0
1
Order By: Relevance
“…Outputs from the general-circulation models cited in IPCC’s five Assessment Reports FAR, SAR, TAR, AR4 and AR5 [1–5] were examined in [6] using a simple model calibrated against IPCC’s central climate-sensitivity estimates in AR4-5 and were found to overestimate observed air temperature trends. Reasons for this hot running were discussed.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Outputs from the general-circulation models cited in IPCC’s five Assessment Reports FAR, SAR, TAR, AR4 and AR5 [1–5] were examined in [6] using a simple model calibrated against IPCC’s central climate-sensitivity estimates in AR4-5 and were found to overestimate observed air temperature trends. Reasons for this hot running were discussed.…”
Section: Introductionmentioning
confidence: 99%
“…In [6], it was concluded that once due allowance is made for these and other shortcomings in the general-circulation models, the likely global warming in response to a doubling of CO 2 concentration is not 3.3 K but 1 K or less and that even if all available fossil fuels are combusted <2.2 K warming will result.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An interesting question is whether reviving this old physics-model in the context of modern data can convince the scientifically literate who still do not acknowledge an AGW. This conceptual model also explains why some contrarian views based on IR flux are flawed (Monckton et al 2015): They do not account for convection. There is a cause for optimism if the reason for different views is 'agnotological' in terms of forgotten ideas (Proctor and Schiebinger 2008).…”
Section: Discussionmentioning
confidence: 89%